Characterization of some techniques of immunofluorescence and fluorescence in chilean mussels Perumytilus purpuratus and Semimytilus algosus - Garrido, Orlando (1999)
Gametes and larval stages of the mussels P purpuratus and S. algosus were treated in vitro with fluorescent and non-luorescent techniques in order to detect microfilaments, DNA and cortical granules involved with reproductive status as fertilization and cleaveage stages. In P. purpuratus tubulin was detected in cilius and velum in D larval stages, also actin was detected from the fertilization to development stages in both P purouratus and S. algosus. Cortical granule-like structures were observed in larval stages of P purpuratus suggesting they are not discharged during the fertilization process. Microfilaments detected in both mussels suggest they play an important role in the cytoskeleton during development.